Bridging the funding gap in public construction projects: a case of Ministry of Local Government, Public Works and National Housing - Madzinga, Justice (Midlands State University, 2017)
The research project is about bridging the fund gap in public construction projects, the case of Ministry of Local government, Public works and National Housing. The research was carried out concurrently with the final semester as a visiting student at the Midlands State University. The major objectives of the study were to establish the existence of the funding policy for construction projects, identifying policy implementation guidelines which are in place, determining controls in place to ensure that the policy implementation guidelines are applied ,to establish whether controls are reviewed for adequacy are in place and to recommend best ways of funding construction projects. The research data was collected through questionnaires and interviewing of the senior officers and management. Questionnaires were distributed to officers in the construction, engineering, administration, audit and accounts departments. The major findings drawn out of the research study were that the management is not operating in compliance with the macroeconomic policy and budget framework, implementation guidelines are not documented and communicated to employees, there is no risk based internal auditors, risk management policy, project managers, ineffective procurement and no risk identification, assessment team and the ministry has not develop public private partnerships. The major recommendations made were that the management should maneuver in compliance with the funding policy as delineated in the macro-economic planning and budget framework, government should document the policy implementation guidance and training be done to communicate the implementation guidelines to employees, government should set up risk based internal auditors ,formulate risk policy, come up with risk identification ,assessment ,management team, appoint project manager and employ network analysis in managing public construction projects, the government develop a public private partnership framework for construction project.